Cesium immobilization into potassium magnesium phosphate matrix - Sayenko, S.Y.; Wagh, Arun S.; Shkuropatenko, V.A.; Bereznyak, O.P.; Hodyreva, Y.S.; Tarasov, R.V.; Virych, V.D.; Ulybkina, Е.А.; Pylypenko, O.V.; Kholomeev, G.O.; Zykova, A.V. (Вопросы атомной науки и техники, 2017)
The possibility of isomorphous substitution of potassium ions by cesium ions in the structure of potassium magnesium phosphate KMgPO₄ ∙ 6H₂O (PMP) was shown. It was established, that the Cs included into the PMP matrix does not transfer to the environment during high temperatures heating process (1176 ºС, 3 hours). Analysis of the IR absorption spectrum of the PMP sample has demonstrated that an increase in the amount of additive of the cesium chloride resulted in the shift of the main bands in the spectrum to the low-frequency region with average shift value 10 cm⁻¹, which indicates the strengthening of bonds in the crystal lattice of matter. The calculated degree of substitution of potassium by cesium during energy release process in the PMP matrix at the level of vitrified high level wastes is about 4%, i. e. the PMP matrix should correspond to the formula K₀̦₉₆Cs₀̦₀₄MgPO₄ · 6H₂O.